1980
DOI: 10.2466/pr0.1980.47.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Police Applicants: A 5-Item MMPI Research Index

Abstract: The usefulness and validity of various personality tests in the selection of police officers has been recently considered. This study examines use of the MMPI to differentiate successfully between acceptable and unacceptable police candidates. An item analysis of the MMPI is presented, and five items which significantly differentiated the groups are combined in an index. The statistical errors of inference in a simulated selection procedure are examined with the use of Bayes theorem. The index has sufficient v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Azen et al (1973) studied 100 newly hired sheriffs in Los Angeles, and concluded that MMPI scores were unsuccessful in predicting dropouts. Research by Schoenfeld et al (1980) and Merian et al (1980) compared groups of problem police performers with a control group. No significant differences between the MMPI profiles of the two groups were detected in either study.…”
Section: The Mmpi Instrument Overviewmentioning
confidence: 99%
“…Azen et al (1973) studied 100 newly hired sheriffs in Los Angeles, and concluded that MMPI scores were unsuccessful in predicting dropouts. Research by Schoenfeld et al (1980) and Merian et al (1980) compared groups of problem police performers with a control group. No significant differences between the MMPI profiles of the two groups were detected in either study.…”
Section: The Mmpi Instrument Overviewmentioning
confidence: 99%